Cadmium and molybdenum co-induce pyroptosis and apoptosis via the PTEN/PI3K/AKT axis in the livers of Shaoxing ducks (Anas platyrhynchos). Issue 4 (3rd February 2022) - Cao, Panpan; Nie, Gaohui; Luo, Junrong; Hu, Ruiming; Li, Guyue; Hu, Guoliang; Zhang, Caiying
Abstract : Cadmium (Cd) and excessive molybdenum (Mo) have adverse impacts on animals. Abstract : Cadmium (Cd) and excessive molybdenum (Mo) have adverse impacts on animals. However, the hepatotoxicity co-induced by Cd and Mo in ducks has not been fully elucidated. In order to explore the impacts of Cd and Mo co-exposure on pyroptosis and apoptosis by the PTEN/PI3K/AKT pathway in the livers of ducks, 40 healthy 7-day-old Shaoxing ducks ( Anas platyrhynchos ) were randomly assigned into 4 groups, and Cd or/and Mo were added to the basic diet per kilogram (kg): control group (0 mg Mo and 0 mg Cd), Mo group (100 mg Mo), Cd group (4 mg Cd), and Mo + Cd group (100 mg Mo and 4 mg Cd), with 16 weeks feed management. Results signified that Cd or/and Mo caused trace element imbalance, liver function and histomorphological abnormalities in the duck liver, and activated the PTEN/PI3K/AKT pathway through increasing PTEN mRNA and protein levels, reducing PI3K, AKT mRNA and p-AKT/AKT protein levels, which triggered pyroptosis and apoptosis via increasing Caspase-1, NLRP3, NEK7, ASC, GSDME, GSDMA, IL-1β and IL-18 mRNA levels, Caspase-1 p20, NLRP3, ASC and GSDMD protein levels, and IL-1β and IL-18 contents, and increasing Bak-1, Bax, Cyt C and Caspase-3 mRNA levels and cleaved Caspase-3/Caspase-3 protein level, and downregulating Bcl-2 mRNA level and the ratio of Bcl-2 to Bax, respectively. Overall, the results illustrate that pyroptosis and apoptosis induced by Cd or/and Mo may be associated with activating the PTEN/PI3K/AKT pathway in the livers of ducks. There may be a synergy between these two elements.